Planning a large‐scale tabletop exercise to test Qatar's healthcare system readiness to respond to a major incident during the 2022 FIFA World Cup - Guillaume Alinier (6952004) (2023)
This article is an illustration of ‘Lessons from the Field’. The Journal of Contingencies and Crisis Management has begun to present lessons coming from professionals engaged in crisis management. ‘Lessons for the Field’ provides insights that can be useful to other professionals. Moreover, ‘Lessons from the Field’ can stimulate ideas for researchers and provide resources for educators. Hosting a mega-sporting event such as the International Federation of Football Associations (FIFA) World Cup presents many healthcare challenges, especially when organized over a small geographical area with many international supporters potentially increasing the country's normal population by 50%. This article presents how a system-wide tabletop simulation exercise was planned to test Qatar's healthcare system's readiness to respond to a potential major incident during the FIFA World Cup. The healthcare system-wide tabletop exercise lasted about 4 h with participants engaging in all the various facilities as expected. It provided opportunities for everyone to put their knowledge of major incident response and mass casualty management into practice. The exercise preparation ensured it ran smoothly for all participants who quickly understood how to engage in the activity. It enabled organizers and participants to identify potential gaps in systems and processes, but also in their own ability to manage such situation. Other Information Published in: Contingencies and crisis management License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1111/1468-5973.12485 Additional institutions affiliated with: National Health Incident Command Centre - HMC and Emergency and Disaster Preparedness - PHCC